Rearticulating Youth Subjectivity Through Gay-Straight Alliances (GSAs) - Herriot, Lindsay (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2014)
Populated by lesbian, gay, bisexual, trans*, queer (LGBTQ) and allied youth, school-based gay straight alliances (GSAs) offer a unique opportunity to re-imagine or redefine youth subjectivity, especially with regards to the intersections of sexual orientation, gender identity, and civic rights. Tracing the evolution of youth subjectivity from the emergence of Canadian schooling in the 1860s, I turn to Ontario’s Bill 13 as a recent example of how GSAs are subverting, or resisting these norms, and in so doing, operate as a kind of counter-public. Drawing from Jenks’ (2005) archetypes of the Dionysian and Apollonian child, I assert that GSAs can embody a third type of child subjectivity, the Athenian child (Smith, 2011; 2014) and, in so doing, provide theoretical space to reconstitute subjectivity for all youth.